Kloning dan Analisis Bioinformatika Gen MSP1 Plasmodium falciparum Isolat Kota Jayapura - Arsyam Mawardi; Leonardo E. Aisoi; Paula N. Lefaan (Jurnal Biologi Papua, 2018)
Cloning gene involves the construction of a recombinant plasmid that inserted in a competent cell. On the other hand, genetic engineering requires bioinformatic analysis to be converted into tabulation and data interpretation. The study, titled "cloning block 2 MSP1 gene of Plasmodium falciparum isolate Jayapura city and bioinformatics analysis" is aimed to improve the technique of cloning the MSP1 gene of P. falciparum, initiated the creation of DH5α competent cells, ligations and transformations, plasmid isolation, confirmation the recombinant plasmid and able to perform bioinformatics analysis and construct phylogenetic tree. This study began with the manufacture of E. coli DH5α competent cells, MSP1 gene ligation in pJET1.2/blunt vector and transformation by using the heat shock transformation method, plasmid isolation of alkali lysis method, then plasmid confirmed by PCR and sequencing method, further sequence analysis and phylogenetic tree construction. The results showed that confirmation of MSP1 gene presence in pJET1.2/blunt with PCR was successful. From a total of 4 positive colonies grown in liquid culture, then isolated plasmid and confirmed with PCR obtained electroferogram bands with a size about 1049 bp indicates the presence of MSP1 gene in plasmid. Based on the results, cloning of MSP1 gene using pJET1.2/blunt cloning vector and competent cell E. coli DH5α has been successfully performed. Bioinformatics analysis of sequencing result and phylogenetic tree were constructed successfully with 2 clusters isolate of malaria patients from Jayapura city. Key words: Bioinformatics, cloning gene, heat shock transformation, MSP1, P. falciparum.